Peran Manajemen Kepala Sekolah dalam Mengembangkan Budaya Belajar yang Inklusif - Darviana, Darviana; Saril, Saril (Jurusan Tarbiyah STAI Al-Gazali Bone, 2024)
Education management requires managerial skills so that educational governance can be optimized to achieve national education goals. School principals as managers need to have good managerial skills, because this really determines the smoothness of the teaching and learning process. The results of the research show that: (1) the management role of the principal at SD Inpres 12/79 Abbumpungeng has so far been carried out well. This can be seen from the school principal's ability to set educational goals, detail learning activities, provide effective direction to teachers, and carry out systematic monitoring of the teaching and learning process, (2) An inclusive learning culture for teachers and students at SD Inpres 12/79 Abbumpungeng has been implemented quite well through a learning culture that has encouraged students to learn independently, increased active involvement in the learning process, and created positive collaboration between regular students and inclusive students, and (3) the management of the principal at SD Inpres 12/79 Abbumpungeng plays an important role in developing an inclusive learning culture to ensure that all students, both regular and special needs, receive the attention and support they need.